2019
DOI: 10.34306/att.v1i2.47
|View full text |Cite
|
Sign up to set email alerts
|

The Online Sales Application Of Black And White Print Based On Yii Framework On Higher Education E-Commerce Website

Abstract: Raharja Internet Cafe as a facility in Raharja College which is provided for Personal Raharja in helping provide the need for lecture activities. Raharja Internet Cafe has a problem that the system of selling black and white print products that apply consumers must come directly to the RIC room at LV-002 at Raharja College, but Raharja Internet Cafe cannot accommodate many consumers because of the limited area. These problems are the background for the establishment of an electronic sales system (e-commerce) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…[23] Macro policies that are prioritized from the results of the ANP process provide an interpretation that political economy policies from poverty alleviation problems are prioritized. [24] This is in line with the construction of the idea that one of the causes of poverty is the distortion of the political economy. The macro strategy is the answer to improving economic policies related to poverty alleviation.…”
Section: Poverty Alleviation Strategysupporting
confidence: 57%
“…[23] Macro policies that are prioritized from the results of the ANP process provide an interpretation that political economy policies from poverty alleviation problems are prioritized. [24] This is in line with the construction of the idea that one of the causes of poverty is the distortion of the political economy. The macro strategy is the answer to improving economic policies related to poverty alleviation.…”
Section: Poverty Alleviation Strategysupporting
confidence: 57%
“…In particular, smart learners can involve many projects that are run on an open data platform such as using collaborative WiFi. [56] Likewise, in [57] the author describes intelligent learning with cloud computing, SOA, and IoT which is managed at the Moncloa International Excellence Campus of Universidad Politécnica de Madrid (Spain). Smart learning is also described in [10], where the author proposes an innovation based on IoT and cloud computing to be applied to the Wuhan University of Technology (China) which is intended to support various applications.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the SCM (supply chain management) system also plays a role in improving the hajj management system. [16] Setyawan concluded that Portfolios in the moderate scenario provide a return of 14,70% and have a risk level of 3,22% per year with a 30% deposit composition, 60% Sukuk, and 5% in stocks and the real sector. Kurniadi Deposit of Hajj funds accumulated due to the limitation of the waiting list and based on management conducted by the Government (BPKH).…”
Section: Previous Studiesmentioning
confidence: 99%